Assessment of the application for renewal of authorisation of Natugrain® Wheat TS and TS L (endo‐1, 4‐beta‐xylanase) as a feed additive for chickens for fattening, ducks, turkeys for fattening, turkeys reared for breeding, minor avian species (except ducks and laying birds) and ornamental birds. (28th March 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Natugrain ® Wheat TS is the trade name for a feed additive that contains endo‐1, 4‐beta‐xylanase produced ■■■■■ The product is currently authorised for use as a feed additive in chickens for fattening, turkeys for fattening or reared for breeding, ducks, ornamental birds and minor avian species (except ducks and laying birds). This scientific opinion concerns the renewal of the authorisation of this additive for those species. The applicant provided evidence that the additive in the market complies with the conditions of the authorisation. According to the information provided by the applicant, no new evidence has been identified that would make the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) reconsider the previous conclusions regarding the safety for the target species, consumer, user and environment under the authorised conditions of use. The additive is safe for the target species for which there is an authorisation, the consumers and the environment. The additive is a potential skin and dermal sensitiser. The present application for renewal of the authorisation did not include a proposal for amending or supplementing the conditions of the original authorisation that would have an impact on the efficacy of the additive. Therefore, there was no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.